Investigating the shared genetic architecture between COVID-19 and obesity: a large-scale genome wide cross-trait analysis - Chen, Yanjing; Fan, Chunhua; Liu, Jun (Frontiers in Endocrinology, 2024)
Observational studies have reported high comorbidity between obesity and severe COVID-19. The aim of this study is to explore whether genetic factors are involved in the co-occurrence of the two traits. Based on the available genome-wide association studies (GWAS) summary statistics, we explored the genetic correlation and performed cross-trait meta-analysis (CPASSOC) and colocalization analysis (COLOC) to detect pleiotropic single pleiotropic nucleotide polymorphisms (SNPs). At the genetic level, we obtained genes that were physically labelled by SNPs using Functional mapping and annotation (FUMA) and the multi-marker genus annotation analysis (MAGMA). Potential functional genes were further investigated by summary-data-based Mendelian randomization (SMR). Finally, the casualty was identified using the latent causal variable model (LCV). A significant positive genetic correlation was revealed between obesity and COVID-19. We found 331 shared genetic SNPs by CPASSOC and 13 shared risk loci by COLOC. At the genetic level, We obtained 3546 pleiotropic genes, among which 107 genes were found to be significantly expressed by SMR. Lastly, we observed these genes were mainly enriched in immune pathways and signaling transduction.These findings could provide new insights into the etiology of comorbidity and have implications for future therapeutic trial.